The Temptation of Graves in Salafi Islam Iconoclasm, Destruction and Idolatry, by Ondrej Beránek and Pavel Tupek. (13th October 2021) - Wagemakers, Joas
Abstract : The Temptation of Graves in Salafi Islam Iconoclasm, Destruction and Idolatry, by Ondrej Beránek and Pavel Tupek. Edinburgh University Press, 2018. 272pp., Hb. £80.00. ISBN-13: 9781474417570.